Independence of Bangladesh in 266 days : history and documentary evidence - Quadir, Muhammad Nurul (Dhaka : Mukto publishers, 2004)
Art, Culture and History
2005-03-22
Keywords: Independence day; Documentary evidence; History; Bangladesh